Analysis of Factors Influencing Rice Imports in Indonesia - Kusmiati; Prasetyo Ari Bowo (Efficient: Indonesian Journal of Development Economics, 2024)
Indonesia is an agricultural country with great potential in producing food commodities. Rice is the most widely consumed food commodity by the Indonesian population, so one of the main tasks of the government is to ensure that the availability of rice can meet the needs of the community. This study aims to analyze the effect of rice production, price of imported rice, urban population growth, and foreign exchange reserves on rice imports in Indonesia in 1985-2021. This research is a type of quantitative research using secondary data obtained from UN Comtrade, FAO, and the World Bank. The research method used is the Error Correction Model (ECM). The results of the study stated that (1) rice production has a significant effect on rice imports in the short and long term, (2) the price of imported rice has a significant effect on rice imports in the short and long term, (3) urban population growth has no significant effect on imports rice in the short term, but has a significant effect on rice imports in the long term, and (4) foreign exchange reserves have a significant effect on rice imports in the short and long term.